SRC signaling is crucial in the growth of synovial sarcoma cells - Michels, Sebastian; Trautmann, Marcel; Sievers, Elisabeth; Kindler, Dagmar; Huss, Sebastian; Renner, Marcus; Friedrichs, Nicolaus; Kirfel, Jutta; Steiner, Susanne; Endl, Elmar; Wurst, Peter; Heukamp, Lukas; et al. (Cancer research, 2013)
Synovial sarcoma is a soft-tissue malignancy characterized by a reciprocal t(X;18) translocation encoding a chimeric transcriptional modifier. Several receptor tyrosine kinases have been found activated in synovial sarcoma; however, no convincing therapeutic concept has emerged from these findings. On the basis of the results of phosphokinase screening arrays, we here investigate the functional and therapeutic relevance of the SRC kinase in synovial sarcoma. Immunohistochemistry of phosphorylated SRC and its regulators CSK and PTP1B (PTPN1) was conducted in 30 synovial sarcomas. Functional aspects of SRC, including dependence of SRC activation on the SS18/SSX fusion proteins, were analyzed in vitro. Eventually, synovial sarcoma xenografts were treated with the SRC inhibitor dasatinib in vivo. Activated phospho (p)-(Tyr416)-SRC was detected in the majority of tumors; dysregulation of CSK or PTP1B was excluded as the reason for the activation of the kinase. Expression of the SS18/SSX fusion proteins in T-REx-293 cells was associated with increased p-(Tyr416)-SRC levels, linked with an induction of the insulin-like growth factor pathway. Treatment of synovial sarcoma cells with dasatinib led to apoptosis and inhibition of cellular proliferation, associated with reduced phosphorylation of FAK (PTK2), STAT3, IGF-IR, and AKT. Concurrent exposure of cells to dasatinib and chemotherapeutic agents resulted in additive effects. Cellular migration and invasion were dependent on signals transmitted by SRC involving regulation of the Rho GTPases Rac and RhoA. Treatment of nude mice with SYO-1 xenografts with dasatinib significantly inhibited tumor growth in vivo. In summary, SRC is of crucial biologic importance and represents a promising therapeutic target in synovial sarcoma. Cancer Res; 73(8); 2518-28. ©2013 AACR.